The Effectiveness of the Outdoor Learning Program in Improving High School Students: Understanding of Sustainable Tourism at Daarut Tauhiid Eco Islamic Boarding School - Nugraha, Verza Aldirindra; Haryadi, Rafly; Elistio, Pijar Dwi; Andari, Rini; Yudha, Eka Sakti (Tourism and Hospitality Essentials Journal, 2023)
AbstractThis case study evaluates the effectiveness of an outdoor learning program in enhancing high school students' understanding of sustainable tourism at Daarut Tauhiid Eco Pesantren in Bandung, Indonesia. The qualitative research utilized observations, interviews, and documentation to assess the outdoor learning program which involved field trips to tourism destinations and interactive activities. The results indicate the outdoor learning program was effective in increasing students' comprehension of sustainable tourism principles, raising environmental awareness, and promoting active participation in sustainable tourism activities. Students developed deeper understandings of tourism impacts on the environment, culture and local economies. They exhibited more environmentally-friendly behaviors and initiative in community tourism projects after completing the program. While the program faced challenges like limited time and resources, the school implemented strategies such as curriculum integration, stakeholder partnerships, and continuous evaluation to overcome these obstacles. The outdoor, experiential learning approach showed potential for developing the knowledge, skills and values needed for a more sustainable tourism industry workforce. Implications include the need for wider adoption of outdoor learning in sustainable tourism education through school-industry-community collaboration. Further research could explore long-term impacts on graduates' sustainable tourism practices. Overall, this innovative pedagogical model can help shape a new generation committed to responsible tourism development.Keywords:  Sustainable tourism education, outdoor learning, environmental education, experiential learning,